2002
DOI: 10.1002/art.10652
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor deficits before and two months after knee arthroplasty

Abstract: Objectives. To quantify the locomotor deficits before and 2 months after a total knee arthroplasty (TKA) in patients with osteoarthritis of the knee, and to compare pre-and postoperative performance. Methods. Locomotor capacity of patients was evaluated using laboratory gait and stair-ascent evaluations (kinematic and kinetic variables, electromyographic activity of 4 muscles of both lower limbs, and spatiotemporal parameters), the timed Up & Go (TUG), and the 6-minute walk (6MW) test. Results. Large locomotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 36 publications
8
87
1
8
Order By: Relevance
“…In addition, during the first few weeks after THR, patients experience hip and knee strength loss and decreased functional capacity, which improve initially, then plateau from 6 months to 1 year. Ouellet and Moffet reported that individuals two months after TKR were 58% slower in completing the timed mobility test compared with healthy controls (32). A minimum of 100 degrees of postoperative knee flexion is desired for a chair rising activity and that a higher chair is more suitable for THR and TKR patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during the first few weeks after THR, patients experience hip and knee strength loss and decreased functional capacity, which improve initially, then plateau from 6 months to 1 year. Ouellet and Moffet reported that individuals two months after TKR were 58% slower in completing the timed mobility test compared with healthy controls (32). A minimum of 100 degrees of postoperative knee flexion is desired for a chair rising activity and that a higher chair is more suitable for THR and TKR patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…Como primeira escolha, o tratamento não-medicamentoso inclui educação do paciente, perda de peso, fisioterapia, programas de condicionamento físico e uso de órteses, associadas ou não ao uso de drogas analgésicas antiinflamatórias. Quando há insucesso do tratamento conservador os pacientes com OA grave são então encaminhados para a cirurgia de Artroplastia Total de Joelho (ATJ) (COIMBRA et al, 2002;OUELLET;MOFFET, 2002;MARX et al, 2006;FACCI et al, 2007).…”
Section: Avaliação Da Efetividade Da Cirurgia De Artroplastia Total Dunclassified
“…Deve ser priorizado o tratamento de reabilitação nas primeiras semanas após o procedimento cirúrgico, afim de obter uma recuperação funcional o mais precoce possível. (OUELLET, MOFFET, 2002;LENSSEN et al, 2003). A fisioterapia convencional de forma bem conduzida pode determinar resultados satisfatórios na reabilitação de pacientes submetidos à ATJ.…”
Section: Avaliação Da Efetividade Da Cirurgia De Artroplastia Total Dunclassified
“…Total knee arthroplasty (TKA) is an effective treatment to reduce pain and subjective disability in patients with osteoarthrosis of the knee, but several studies have shown that muscle strength deficiency [1][2][3] and functional limitations may persist for several years after the operation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%